Role Ambiguity in Families and Parenting Efficacy: The Mediating Role of Spousal Support - Gong, Jiaowei; Santoso, Agu (Applied Family Therapy Journal (AFTJ), 2025)
Objective: This study aimed to examine the mediating role of spousal support in the relationship between role ambiguity and parenting efficacy among Indonesian parents. Methods and Materials: A descriptive correlational design was employed with 390 married parents recruited from community centers and networks across Indonesia. The sample size was determined using the Morgan and Krejcie table. Data were collected using standardized instruments for role ambiguity, spousal support, and parenting efficacy. Analyses included Pearson correlation coefficients using SPSS-27 to assess bivariate associations and structural equation modeling (SEM) with AMOS-21 to test the hypothesized mediation model. Model fit was evaluated using χ², χ²/df, CFI, TLI, GFI, AGFI, and RMSEA indices. Findings: Results revealed that role ambiguity was significantly and negatively correlated with both spousal support (r = –.41, p < .01) and parenting efficacy (r = –.36, p < .01). Spousal support was positively correlated with parenting efficacy (r = .52, p < .01). The SEM demonstrated good model fit (χ²/df = 1.94, CFI = .96, TLI = .95, RMSEA = .049). Path analysis showed that role ambiguity had a direct negative effect on parenting efficacy (β = –.24, p < .01) and spousal support (β = –.38, p < .01), while spousal support had a direct positive effect on parenting efficacy (β = .41, p < .01). Moreover, spousal support partially mediated the effect of role ambiguity on parenting efficacy through a significant indirect pathway (β = –.16, p < .01). Conclusion: The study confirms that role ambiguity undermines parenting efficacy both directly and indirectly, while spousal support strengthens parental confidence and mitigates the negative effects of unclear family roles. These findings highlight the importance of enhancing spousal support and clarifying family roles to foster effective parenting in collectivist contexts such as Indonesia.